(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Accurate detection of astrocytomas is very difficult. Objective: The purpose of the present study was to evaluate the usefulness of MRI in detection of intracranial astrocytoma. Methodology: This cross-sectional study was carried out in the Department of Radiology and Imaging with the collaboration of Department of Neurosurgery and Department of Pathology at Sir Salimullah Medical College (SSMC & MH), Dhaka from January 2013 to December 2013 for a period of one (1) year. Prior to the commencement of this study, the research protocol was approved by the ethical committee (Local Ethical committee) of SSMC. All the patients presented with clinically diagnosed cases of intracranial astrocytoma who were attended in the OPD and IPD were included as study population. The sampling technique was purposive, non-random sampling method. MRI was performed in all cases. The postoperative resected tissues were examined histopathological in the respective department. Then the collected reports were compared with findings of MRI. Results: The sample size of the present study was 48 astrocytoma patients. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of MRI for the diagnosis of astrocytoma are 92.0%, 80.0%, 96.0%, 67.0% and 90.3% respectively. Conclusion: In conclusion MRI has a high diagnostic validity for the detection of astrocytoma. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):63-67